Effect of graphene nanosheets and bismuth oxide nanoparticles on the thermal and mechanical properties of K-carrageenan films - Escuadro, Cathy B. (Animo Repository, 2024)
With the health and environmental hazards associated with conventional fossil-based packaging materials and the demand for advanced thermal packaging technology, this study has developed biobased nanocomposite films by integrating graphene nanosheets (GNS) and Bismuth Oxide Nanoparticles (Bi2O3 NPs) into the K-Carrageenan biopolymer matrix. GNS were synthesized using chemical exfoliation and Bi2O3 NPs through hydrothermal technique. Nanofilms were fabricated in three different concentrations via the facile solution casting technique to examine the influence of the nanofillers: K-CGBi (with 3% GNS and 5% Bi2O3 NPs), K-CG (with 3% GNS), and K-C (neat polymer matrix). Scanning electron microscopy coupled with elemental dispersive X-ray was used to examine its surface morphology and elemental composition, and Fourier transform infrared spectroscopy for its chemical composition and compatibility. Thermogravimetric analysis and differential scanning calorimetry were utilized, and thermal conductivity was measured to evaluate their thermal properties. Results show that the nanofillers were successfully embedded in the matrix and uniformly distributed with minimal agglomeration. The addition of nanofillers has shown improved thermal stability, as demonstrated by its TGA. Moreover, DSC reveals an increasing shift in endothermic and exothermic peaks - with the highest shift in its onset temperature observed from K-CGBi, affording better resistance to thermal degradation. Similarly, its thermal conductivity showed a notable increase at 59% for K-CGBi and 8.59% for K-CG compared to the neat K-C film. Furthermore, K-CGBi and K-CG composite films exhibited improved mechanical properties with 56% and 25% enhancement of tensile strength but a 28% and 21% reduction in elongation at break, respectively. Considering these, the fabricated films can potentially be applied for thermal packaging applications.